Il deperimento dei geomateriali da costruzione: implicazioni sulla capacità sismica residua di edifici in CA e muratura ordinaria - Marani, Federica <1980> (Alma Mater Studiorum - Università di Bologna, 2011)
This work is dedicated to the study of damaging phenomena involving reinforced concrete structures and masonry buildings and the consequences in terms of structural performances decay. In the Italian context there are many examples of structures that have already exceeded their service life, considering not only the ancient buildings but also infrastructures and R/C buildings that today are operating from more than 50th years. Climate change which is subject to the entire planet, with changing in seasonal weather and increasing in environmental pollution, is not excluded could have a harmful influence on the rate of building materials decay previously deemed as durables. If the aggressive input changes very fast, for example in a few decades, then it can also change the response of a construction material considered so far durable; in this way the knowledge about the art of good build, consolidated over the centuries, is thwarted. Hence this study is focused on the possibility to define the residual capacity for vertical or seismic loads for structures that are already at the limit of their service life, or for which is impossible to define a service life. The problem in an analysis of this kind, and that is what makes this research different from the main studies avaibles in the literature, is to keep in correlation – in a not so expensive computationally way – issues such as: - dangerous environmental inputs adequately simulated; - environmental conditions favorable to the spread of pollutants and development of the degradation reactions (decay’s speed); - link between environmental degradation and residual bearing capacity A more realistic assessment of materials residual performances that constitute the structure allows to leave the actual system for the residual load-bearing capacity estimation in which all factors are simply considered through the use of a safety factor on the materials properties.